2019
DOI: 10.1038/s41598-019-49111-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toll-like receptors as prognostic biomarkers in gastric cancer: high tissue TLR5 predicts a better outcome

Abstract: Toll-like receptors (TLRs), key proteins in innate immunity, appear to contribute to the inflammatory environment in carcinogenesis. Thus, we aimed to evaluate the tissue expressions of TLR1, TLR2, TLR4, TLR5, TLR7, and TLR9 as potential prognostic biomarkers in gastric cancer. We applied immunohistochemistry to study tissue samples from 313 patients operated on for gastric adenocarcinoma between 2000 and 2009 at the Department of Surgery, Helsinki University Hospital, Finland. A high expression of each TLR st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
(30 reference statements)
3
21
0
Order By: Relevance
“…29 At the same time, Kasurinen et al unexpectedly found that the expression of TLR7 was significantly related to STAD stage (p = 0.03). 30 Similarly, our results revealed that both the transcriptional and translational levels of TLR7 were significantly elevated in patients with STAD compared to healthy controls. Meanwhile, the expression of TLR7 was significantly associated with STAD stage and grade.…”
Section: Discussionsupporting
confidence: 72%
“…29 At the same time, Kasurinen et al unexpectedly found that the expression of TLR7 was significantly related to STAD stage (p = 0.03). 30 Similarly, our results revealed that both the transcriptional and translational levels of TLR7 were significantly elevated in patients with STAD compared to healthy controls. Meanwhile, the expression of TLR7 was significantly associated with STAD stage and grade.…”
Section: Discussionsupporting
confidence: 72%
“…4d). TLR4 has been found to be highly expressed in GC and can be employed as a biomarker for GC [9,17]. StarBase analysis confirmed that TLR4 was highly expressed in GC and the expression of miR-365 and TLR4 was significantly negatively correlated (Fig.…”
Section: Mir-365 Inhibits Gastric Precancerous Lesions By Inhibiting mentioning
confidence: 78%
“…Thus, it has recently been shown that counts of urinary T-cell, renal tubular epithelial cells, and podocalyxin-positive cells provide an excellent biomarker for the detection of renal transplant rejection in routine clinical trials [3]. Currently, the role of TLR receptors as potential marker molecules for the development of neoplastic diseases is emphasized more and more often, e.g., TLR5 as a prognostic marker for gastric cancer [4]. It was also shown that the activity of TLR receptor is correlated with the state of injury of post-surgical patients who have a disorder of the immune response related to the interaction of TLR receptors with DAMP (damage-associated molecular pattern).…”
Section: Introductionmentioning
confidence: 99%